2021 Comprehensive Surveillance Review : Background Paper on Main Findings from The Stakeholder Surveys. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2021)
This note presents key results from the surveys of country authorities, IMF Executive Directors (EDs), and mission chiefs (MCs) to inform the Comprehensive Surveillance Review (CSR). Key takeaways and cross-cutting themes that emerge are Trends, Policy Challenges, Surveillance Priorities, Surveillance modalities and Traction.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Aggregate Factor Income Distribution; Monetary Policy; Political Economy